2020
DOI: 10.20961/jab.v20i2.525
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Accounting Knowledge in Moderating Relationship between Understanding and Socialization of Tax Toward MSMEs Tax Compliance

Abstract: This research aims to analyze the understanding and socialization of taxation on tax compliance of MSMEs. This research also aims to analyze the influence of understanding of accounting in moderating the relationship of understanding and socialization of taxation on tax compliance of MSMEs. Samples were determined by the stratified cluster sampling method. The number of respondents is 151 MSMEs owners/managers/actors in sectors of the trade, hotel, and restaurant. This study uses the Structural Equation Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…By increasing awareness and promoting better comprehension through socialization, it can lead to higher levels of taxpayer compliance (Nono & Tyas, 2023). The researched findings of Rahayu et al (2020) and Lestary et al (2021) indicates a positive influence of socialization on the compliance of MSME taxpayer. Based on the information provided earlier, the researcher developed the following hypothesis: H2: The tax socialization has a positive and significant effect on the compliance of MSME taxpayer…”
Section: The Effect Of Tax Socialization On the Compliance Of Msme Ta...mentioning
confidence: 81%
See 1 more Smart Citation
“…By increasing awareness and promoting better comprehension through socialization, it can lead to higher levels of taxpayer compliance (Nono & Tyas, 2023). The researched findings of Rahayu et al (2020) and Lestary et al (2021) indicates a positive influence of socialization on the compliance of MSME taxpayer. Based on the information provided earlier, the researcher developed the following hypothesis: H2: The tax socialization has a positive and significant effect on the compliance of MSME taxpayer…”
Section: The Effect Of Tax Socialization On the Compliance Of Msme Ta...mentioning
confidence: 81%
“…Through these mediums, individuals can gain a better understanding of tax-related information, leading to increased taxpayer awareness and compliance (Rahmawati, 2022). Previous studies by Rahayu et al (2020) and Lestary et al (2021) indicates a positive influence of socialization on the compliance of MSME taxpayer. In contrast to two previous researchers, Afriani et al (2022) found that socialization didn't impact the compliance of MSME taxpayer.…”
Section: Introductionmentioning
confidence: 82%
“…Path coefficients indicate the direction of positive or negative influence in the independent variable on the dependent. At the same time, the significance value shows whether or not the probability value of the influence of the independent variable is significant on the dependent (Rahayu, Bawono, & Sudibyo, 2020). The hypothesis in this study is as follows: 1.…”
Section: Introductionmentioning
confidence: 90%